Complanatuside alleviates inflammatory cell damage induced by pro-inflammatory cytokines in skin keratinocytes - Xiao Wang; Xuetao Xu; Xuetao Xu; Panpan Wu; Panpan Wu; Mengshuo Wu; Lishe Gan; Lishe Gan; Jingwei Jin; Rihui Wu; Wenfeng Liu; Kun Zhang; et al. (Frontiers in Chemistry, 2022)
Cytokine-mediated inflammatory response is considered a cause of skin lesion in COVID-19 patients. Complanatuside is a flavonol glycoside isolated from Astragalus complanatus. Flavonoids from Astragalus complanatus were reported to have anti-inflammatory and anticancer activities but the potential protective effect of complanatuside on cytokine-induced inflammatory damage in skin keratinocytes is not known. The aim of this study is to explore the inhibitory effect of complanatuside on inflammation and its underlying mechanisms in skin epithelial HaCaT cells treated with inflammatory cytokines. The combination of IFN-γ, TNF-α, and IL-6 decreased cell viability, increased cell death, and pyroptosis in HaCaT cells. Treatment with complanatuside alleviated the effects of the cytokine combination on HaCaT cells. Complanatuside down-regulated pyroptosis related to NLRP3, GSDMD, and ASC. The effects of complanatuside were related to vast reductions in the levels of iNOS, COX-2, and ROS. Results of the present study indicate that complanatuside inhibited inflammation and protected the cells from inflammatory cell damage in HaCaT cells treated with the combination of IFN-γ, TNF-α, and IL-6. Complanatuside may be a promising candidate for inhibiting COVID-19 related skin inflammatory damage.